House Prices and Macroprudential Policies : Evidence from City-level Data in India. (Washington, D.C. : International Monetary Fund, 2020)
This paper examines the efficacy of macroprudential policies in addressing housing prices in a developing country while underscoring the importance of fundamental factors. The estimated models using city-level data for India suggest a strong influence of fundamental factors in driving housing prices. There is compelling evidence of the effectiveness of macroprudential tools viz., Loan-to-value (LTV) ratio, risk weights, and provisioning requirements, in influencing housing price movements. A granular analysis suggests an even stronger impact on housing prices of a change in the regulatory LTV ratio for large-sized vis-a-vis small-sized mortgages, which buttresses their potency in fighting house price speculations. A tightening of the risk weights on the housing assets of banks causes significant downward pressure on house prices. Similarly, regulatory changes in standard asset provisioning on housing loans also influence house prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet